Effects of commercial fishing operation on the municipality fisherfolks of Miag-ao, Iloilo - Bianet, Hector C. (1998.)
This is a study about the effects of commercial fishing operation on the municipal fisherfolks of Miagao, which focuses particularly on the social and economic aspects. This is a descriptive study which aims to describe the fishing technology, the social and economic characteristics, then determine the socio-economic effects of commercial fishing operation on the municipal fisherfolks of Miagao. Interview of key respondents and archival research were conducted to obtain data and related information about the topic. The results of the study show that in the social aspect, operation of commercial fishing has no significant effect on the municipal fisherfolks. In the economic aspect, however, the operation of commercial fishing has brought about a tremendous effects on the municipal fisherfolks' catch. A reduce in the quantity and quality, in particular.
Thesis (Undergraduate, Bachelor of Arts in Community Development) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Fish and fishing -- Miag-ao, Iloilo